2017
DOI: 10.14739/2409-2932.2017.2.103517
|View full text |Cite
|
Sign up to set email alerts
|

Physical-chemical properties of 5-(3-fluorophenyl)-4-amino-1,2,4-triazole-3-thiol s-derivatives

Abstract: Фізико-хімічні властивості S-похідних 5-(3-фторфеніл)-4-аміно-1,2,4-тріазол-3-тіолуЗапорізький державний медичний університет, УкраїнаСьогодні серед багатьох учених користується популярністю спроба поєднання гетероциклу 1,2,4-тріазолу з різними фармакологічно активними фрагментами інших органічних молекул. Раніш нами відзначалось, що введення до структури 1,2,4-тріазолу фторфенільного радикала призводить до формування нових властивостей сполук, а це, своєю чергою, стимулює та надихає учених на пошук нових речо… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…1), which were first synthesized in the laboratory of organic synthesis of the Department of Natural Sciences for foreign students and toxicological chemistry of Zaporizhzhia State Medical and Pharmaceutical University. Physical-chemical constants of the synthesized compounds have been studied and described before, some of them are given in the literature [1,10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1), which were first synthesized in the laboratory of organic synthesis of the Department of Natural Sciences for foreign students and toxicological chemistry of Zaporizhzhia State Medical and Pharmaceutical University. Physical-chemical constants of the synthesized compounds have been studied and described before, some of them are given in the literature [1,10].…”
Section: Methodsmentioning
confidence: 99%
“…The achievements of Ukrainian scientists in the field of synthetic organic chemistry significantly contribute to the development of world science. Among the variety of known organic compounds, the heterocyclic system of 1,2,4-triazole deserves special attention, as it has been at the center of research for decades [1,2,5]. The 1,2,4-triazole cycle has unique properties, which make it a very attractive target for research [3,4].…”
Section: Original Researchmentioning
confidence: 99%
“…The compounds 1, 2, 3a-f, 4a-f were synthesized on the Department of Natural Sciences for Foreign Students and Toxicological Chemistry of Zaporizhzhia State Medical University, according to a known procedure [12]; the compounds were further used in the investigation of their antimicrobial activity [14,15].…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of this indicator in toxicological studies makes it possible to identify the target organ of the toxicant, to identify signs of endocrine-related effects. The unique properties of 1,2,4-triazole make this heterocycle very attractive for research (Bihdan et al, 2019;Hunchak et al, 2020). Studies have shown the high reactivity and low toxicity of 1,2,4-triazole derivatives and the prospect of their use as potential biologically active compounds.…”
Section: Features Of Experimental Modeling Of Tuberculosismentioning
confidence: 99%
“…The advent of 1,2,4-triazole drugs has revolutionized the treatment of people with invasive and fungal infections (Neofytos, 2010;Haegler et al, 2017;Gotsulia et al, 2018;Zazharskyi et al, 2019). However, keep in mind that drugs with a fragment of triazole can cause various side effects and can sometimes interact with other drugs (Samelyuk & Kaplaushenko, 2015;Fard et al, 2016;Bihdan et al, 2019;Palchykov et al, 2020). Haegler et al (2017) noted that in HepG2 cells (human hepatocarcinoma), posaconazole and ketoconazole were cytotoxic starting at 20 and 50 μM, and decreased cellular ATP content starting at 5 and 10 μM.…”
Section: Introductionmentioning
confidence: 99%